Menopausal women – what are their partners like? Part I. Demographic evaluation and endocrinological status of men - Jakiel, Grzegorz; Pilewska-Kozak, Anna B.; Melaniuk, Mirosław; Tobor, Ewa (Menopause Review/Przegląd Menopauzalny, 2008)
A review of biological, psychological and social status of menopausal women’s partners was done. We gathered data concerning demographic and endocrine status. Basic demographic data suggest that a menopausal woman’s partner is usually 52-60 years old, it is his first formal relationship, which has lasted 25-30 years, his children are older than 25. His life expectancy is about 20 years and is about 10 years shorter than his female partner. Nevertheless such a perspective does not influence daily life. In this period deterioration of endocrine function and gradual decrease of testosterone level in the blood with parallel increase of testosterone binding protein is observed. The result of this process is a diminished amount of biologically active androgens. Similarly, the level of DHEA and its sulphate becomes lower. The rate of the testosterone decrease process between 40 and 70 years of age is estimated as 1% per year. Typical signs and symptoms of lack of androgens include memory deterioration, loss of pubic hair, sadness, grumbling, loss of endurance, loss of facial hair, and job-related problems. In 2005 “Recommendations concerning diagnosis and treatment of late-onset male hypogonadism” were published. Late-onset hypogonadism is defined as a decrease of testosterone level below 346 ng/dl accompanied by clinical symptoms. This syndrome differs from female menopause. The basic difference is that female menopause is a normal period of a woman’s life while late hypogonadism is a disease caused by the insufficiency of testis function. Only a part of the population is affected by late-onset hypogonadism (LOH): 21% of men aged 55-59, 26% of those aged 60-69 and 31% of those aged 70-86. Thus the menopausal woman’s partner may be, but is not necessarily, affected by late hypogonadism.